Communication Immediacy: Behaviors and Perception in a Thai Instructional Context - Wiengnil, Atitaya; Singhakowinta, Jaray (NIDA Journal of Language and Communication, 2025)
Teachers’ communication immediacy arguably fosters and maintains positive relationships between teachers and students. Recognizing that not all communicative behaviors are universally consistent or understood, this study aimed to investigate instructors’ immediacy behaviors and students’ perceptions of the effectiveness of those behaviors in inducing their perceived immediacy in a Thai university. The participants were 234 undergraduate students and two instructors. The collection of research data employed direct observation, questionnaires, and focus group interviews. The findings showed the engagement in various immediacy behaviors of the teachers at different levels of frequency. Students perceived the effectiveness of their teachers’ immediacy behaviors in inducing their perceived immediacy which resulted in reducing interpersonal distance between teachers and students. Cultural influences, in addition to the implication of the findings, were discussed.